2019
DOI: 10.5194/acp-2019-852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seawater Analysis by Ambient Mass Spectrometry-Based Seaomics and Implications on Secondary Organic Aerosol Formation

Abstract: <p><strong>Abstract.</strong> A transmission mode-direct analysis in real time-quadrupole time of flight-mass spectrometry (TM-DART-QTOF-MS)-based analytical method coupled to multivariate statistical analysis was developed to interrogate lipophilic compounds in seawater samples without the need of desalinization. An untargeted metabolomics approach addressed here as seaomics was successfully implemented to discriminate sea surface microlayer (SML) from underlying wate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…21a; all data listed in Table S4). While comparable SML data are lacking for this oceanic province, our data are in range with previous reports for surface water of subtropical regions (Zäncker et al, 2018). A strong day-to-day variability of absolute cell numbers was partly observed (e.g., the decline between 25 and 26 September), but all these changes were found in both the SML and bulk water (Fig.…”
Section: Bacterial Abundance In Distinct Marine Samples: Field and Tasupporting
confidence: 90%
See 4 more Smart Citations
“…21a; all data listed in Table S4). While comparable SML data are lacking for this oceanic province, our data are in range with previous reports for surface water of subtropical regions (Zäncker et al, 2018). A strong day-to-day variability of absolute cell numbers was partly observed (e.g., the decline between 25 and 26 September), but all these changes were found in both the SML and bulk water (Fig.…”
Section: Bacterial Abundance In Distinct Marine Samples: Field and Tasupporting
confidence: 90%
“…The coupling of the DART ion source to high-resolution instrumentation allowed for generating elemental formulae for unknown species, and tandem MS capability contributed to the identification process. Tentative identification of discriminant species and the analysis of relative compound abundance changes among sample classes (SML and bulk water) suggested that fatty alcohols, halogenated compounds and oxygenated boron-containing organic compounds may be involved in water-air transfer processes and in photochemical reactions at the water-air interface of the ocean (Zabalegui et al, 2019). These identifications (e.g., fatty alcohols) agree well with the abundance of lipids in the respective samples.…”
Section: Seawater Untargeted Metabolomicsmentioning
confidence: 64%
See 3 more Smart Citations